WAYS TO IMPROVE THE COMPANY’S CASH FLOW MANAGEMENT - Imanbayeva Zauresh Otegenkyzy; Kusainov Halel Haimullievich; Zhakupova Bakitgul (Academic Journal of Physical and Chemical Sciences, 2020)
In a market economy, the company’s cash flow is the most limited resource, so effective cash management ensures financial stability in the process of enterprise development. The study of cash flow management is aimed at generating information about the direction and sources of cash flow, time parameters, and volumes. This information is necessary to justify decisions about managing cash flows, taking into account the influence of objective and subjective, internal and external factors. Cash flows of an enterprise require the organization of their turnover, use, distribution, and formation. Therefore, the company’s cash flow management system, based on the principle of integration, complexity, orientation and variability, is very necessary, since this is one of the important stages of the company’s activity, which creates the basis for achieving and developing large final results. Management of the organization’s cash flows is carried out within the framework of operational goals aimed at increasing the market value of the enterprise, along with strategic goals that allow you to develop a set of tactical and short-term planning tasks that allow you to determine the optimal level of funds.